Antibacterial and nematocidal activities of extracts of plants of the families Poaceae, Cyperaceae, Asparagaceae, Convolvulaceae, Crassulaceae, Rosaceae, Lamiaceae, and Boraginaceae - Zazharskyi, V. V.; Brygadyrenko, V. V.; Zazharska, N. M.; Boyko, O. O.; Borovik, I. V.; KulishenkoO. М.; DavydenkoP. О. (Regulatory Mechanisms in Biosystems, 2026)
Plant-based drugs are broadly used against microorganisms that cause diseases in people and animals. Nonetheless, their potential has not yet been studied to the fullest. In in vitro conditions, we tested ethanol extracts from the leaves, stems, and roots of 20 species of plants against ten species of bacteria, one fungus, and free-living stages of larvae of ruminant nematodes (L1 Muellerius capillaris, L1–3 Strongyloides papillosus, L3 Haemonchus contortus). Eight-millimeter growth inhibition zones of the colonies were produced by the following ethanol extracts: shoot-and-leaf and root extracts of Prunus fruticosa against eight species of microorganisms (Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Shigella flexneri, Pseudomonas aeruginosa, Enterococcus faecalis, Staphylococcus aureus, and Bacillus subtilis); shoot-and-leaf and root extracts of Salvia nutans – against eight species (E. coli, P. mirabilis, E. faecalis, Listeria monocytogenes, S. aureus, B. subtilis, Clostridium perfringens, and Candida albicans); shoot-and-root extract of Hylotelephium telephium – against seven species (E. coli, K. pneumoniae, P. mirabilis, Sh. flexneri, P. aeruginosa, E. faecalis, and B. subtilis); shoot-and-leaf and root extracts of Koeleria gracilis – against six species (K. pneumoniae, P. mirabilis, E. faecalis, L. monocytogenes, S. aureus, and B. subtilis); shoot-and-leaf and root extracts of Asparagus officinalis – against six species (P. mirabilis, Sh. flexneri, P. aeruginosa, L. monocytogenes, C. perfringens, and C. albicans); shoot-and-leaf extract of Cuscuta sp. – against six species (K. pneumoniae, P. mirabilis, Sh. flexneri, L. monocytogenes, C. perfringens, and C. albicans); leaf, fruit, and root extracts of Prunus spinosa – against six species (E. coli, P. mirabilis, P. aeruginosa, E. faecalis, S. aureus, and B. subtilis); shoot-and-leaf and root extracts of Salvia nemorosa – against six species (E. coli, P. aeruginosa, E. faecalis, L. monocytogenes, S. aureus, and C. perfringens); shoot-and-leaf extract of Carex hirta – against five species (K. pneumoniae, P. mirabilis, P. aeruginosa, L. monocytogenes, and B. subtilis); shoot-and-leaf and root extracts of Stachys sylvatica – against four species (Sh. flexneri, L. monocytogenes, C. perfringens, and C. albicans); and leaf, stem, seed, and root extracts of Lithospermum officinale were effective against four species of microorganisms (E. coli, L. monocytogenes, S. aureus, and B. subtilis). However, the nematocidal action of the alcohol extracts of the studied plants was produced by only two plants: Stachys recta and Lithospermum officinale. Thus, as a result of 24 h exposure to the 0.1% solutions of extracts from these plants, mortality was observed in 46.9% and 59.2% of the cases, respectively. Nonetheless, based on the results of the study, these plants were recognized as promising for further research on in vivo nematocidal activity. During the search of antibacterial and antifungal activities, less promising were the extracts from the following plants: the shoots and leaves, and roots of Setaria viridis, Phlomoides tuberosa, Marrubium vulgare, and the roots of Poa trivialis, Calamagrostis epigejos, and Convolvulus arvensis.